Disaster aid and support for mandatory insurance: Evidence from a survey experiment - Nicola Garbarino; Sascha Möhrle; Florian Neumeier; Marie-Theres von Schickfus (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2024)
Dealing with the consequences of climate change will put an increasing burden on public and private finances. We use the example of floods in a survey experiment among 8,000 German households to elicit households' preferences for climate adaptation policies. In Germany, as in many countries, we observe low insurance penetration in combination with high ex-post state aid in case of large events. We find that prior expectations of flood aid, conditional on severe flooding, are low. Providing information about high ex-post aid increases support for a mandatory flood insurance scheme, which is seen as fairer compared to public aid. We also show that this result is driven by respondents updating their expectations, and reactions are stronger among uninsured households in low-risk areas. In contrast, information about announcements to cut flood aid does not significantly alter expectations and views. We conclude that fairness concerns are relevant in the discussion of public and private responsibilities in dealing with climate change.
Keywords: G52; H23; H84; Q54; 330; Climate change; public aid; mandatory insurance; survey experiment